Efficacy of intravitreal injection of Lucentis in the treatment of diffuse diabetic macular edema associated with pan-retinal photocoagulation in proliferative diabetic retinopathy - L. N. Boriskina; M. Y. Guro; V. N. Potapova; I. A. Melichova; V. R. Polyakova (Офтальмохирургия, 2015)
Purpose. To evaluate the efficacy of intravitreal injection of Lucentis in the treatment of diffuse diabetic macular edema (DME) associated with pan-retinal photocoagulation in the proliferative diabetic retinopathy (DR).Material and methods. A retrospective study (58 eyes) with a high diffuse DME and proliferative DR was performed in 46 patients with insulin-dependent diabetes mellitus aged 45-73 years (mean age: 59.2±0.9 years). All participants underwent i ntravitreal injection (IVI) of Lucentis pars plana. The pan-retinal photocoagulation (PRPC) stage was performed 2 weeks after each Lucentis IVI. The main criteria were the dynamics of best corrected visual acuity (BCVA), the OCT parameters – in the central retinal thickness (1mm) area and volume of the macula. The treatment efficacy was assessed one month after the final PRPC stage.Results and discussion. At the end of treatment an increase in the average BCVA values from 0.32 to 0.45, a decrease in retinal thickness in fovea zone – from 506.9mm to 394.6mm, in the volume of macula from 12.9 to 11.6mm3 were noted. Stabilization or an increase in initial visual acuity was observed in 83.4%. The initial thickness of the retina in the region of 1mm was reduced from 506.9mm to 394.6mm, i.e. decreased by an average of 22%. The stabilization of visual functions was achieved more than in 80% of cases one month after the combi ned treatment.Conclusions. The performed retrospective study showed an efficacy of intravitreal injection of Lucentis to stabilize visual functions, to reduce the height of macular edema during the pan-retinal photocoagulation in patients with proliferative diabetic retinopathy.